Antibacterial Activity and Phytochemical Screening of Ethanol Extract of Cashew Leaves A. occidentale L. Against Escherichia coli - Eka Astuty; Rolan Aponno; Is I. Hataul (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: All parts of the cashew tree Anacardium occidentale L. (especially the leaves and bark) have been widely used as traditional herbal medicines, and are used throughout the world. Thus, in recent decades, the traditional medicinal properties of the Anacardium plant, and its various biological effects are being studied extensively. Purposes: This study aimed to conduct a preliminary study of the antibacterial properties and phytochemical screening of the ethanol extract of cashew leaves. Methods: The antibacterial test of was determined by the Kirby-Bauer disc paper diffusion method. Qualitative test of phytochemical content was carried out using chemical reagents. Results: The results indicated that the ethanol extract of cashew leaves has an inhibitory effect on the growth of Escherichia coli. The smallest inhibition zone was found in the extract with a concentration of 10% of 5.75 mm and the largest was found at a concentration of 100% with a diameter of 14 mm. The phytochemical screening revealed that extracts contained; alkaloids, flavonoids, steroids, terpenoids, phenolics, saponins, and tanins Conclusions: The ethanol extract of cashew leaves was able to inhibit the growth of Escherichia coli test bacteria at all concentration variations. Phytochemical screening also found that the ethanol extract of cashew leaves contains alkaloids, flavonoids, steroid terpenoids, phenolics, saponins, and tannins which are known to have antibacterial properties.